Ulasan Sistematik: Marka Molekular Penanda Patogenitas dan Sebaran Inang Pada Virus Avian Influenza H5N1 - Adam, Kindi; Wulandari, R.Aj. Sri (Jurnal Biotek Medisiana Indonesia, 2013)
The epidemic arising out of H5N1 virus infection causes death case and material loss. Mutation of H5N1 virus that signify the increase of pathogenicity and change of dispersal of host response can be used to reference for early warning system of epidemic caused of avian influenza virus. The objective of this research is to obtain information related to molecular markers of pathogenicity of avian influenza. Reference searching is use to collect information about molecular markers related to pathogenicity. The keywords used on this study are: Avian influenza, H5N1, mutation, Pathogenicity, HA, NA, PB, PA, and NS. Thirty three research papers, 4 reviews and 1 scientific seminar are used on this research. The HA, NA and NS genes was reported to be an important gene that have molecular marker related to increase ofpathogenicity. Whereas HA, PB1, PB2 and PA genes was related to the adaptive ability and the dispersal of host of avian influenza virus. There is 30 amino acid that sign as molecular markers of pathogenicity of avian influenza H5N1. Mutation on 30 molecular markers of HA, NA, PB and NS genes can be used as predictor to anticipate mutation orientation of avian influenza virus to become highly pathogenic and host alteration.Thereby, virus mutation to become highly pathogenic can be anticipated early.Keybwords : Highly pathogenic avian Influenza, Mutation, Molecular Marker, Pathogenicity. HA, NA, PB, NSÂ AbstrakEpidemi akibat virus H5N1 telah menimbulkan banyak korban jiwa dan materi.Mutasi virus H5N1 yang menandakan peningkatan patogenitas dan perubaan sebaran inang dapat dijadikan acuan untuk sistem deteksi dini kewaspadaan epidemi akibat virus avian influenza. Penelitian ini bertujuan mendapatkan informasi terkait dengan marka molekular penanda patogenitas virus avian influenza H5N1. Ulasan sistematis ini dilakukan dengan penelusuran literatur menggunakan Google scholar dan PubMed. Kata pencarian yang digunakan adalah Avian influenza, H5N1, mutation, Pathogenicity, HA,NA,PB,PA,NS. Referensi yang digunakan adalah 33 jurnal, 4 ulasan penelitian dan 1 seminar ilmiah dari dalam dan luar negeri. Gen HA, NA dan NS merupakan gen penting yang memiliki penanda molekuler yang berkaitan dengan peningkatan patogenitas virus avian influenza. Sedangkan gen PB1, PB2 dan PA berhubungan dengan adaptasi dan perubahan rentang inang. Jumlah penanda patogenitas pada gen HA, NA, PB dan NS adalah 30 asam amino. Mutasi pada 30 marka genetik gen HA, NA, PB dan NSmerupakan penanda molekular yang dapat digunakan sebagai panduan awal untuk mengantisipasi arah mutasi virus avian influenza menuju pergeseran rentang inang dan peningkatan patogenitasnya. Dengan demikian, perubahan virus avian influenza menjadi bersifat higly pathogenic dapat diantisipasi lebih dini.Kata kunci : Highly pathogenicavian Influenza, Mutasi,Marka Molekular, Patogenitas., HA, NA, PB, NS.